A Premature Rise of Luteinizing Hormone Is Associated With a Reduced Cumulative Live Birth Rate in Patients ≥37 Years Old Undergoing GnRH Antagonist In Vitro Fertilization Cycles - Gao, Fumei; Wang, Yanbin; Wu, Dan; Fu, Min; Zhang, Qiuxiang; Ren, Yumeng; Yang, Zexi; Shen, Huan; Han, Hongjing (Frontiers in Endocrinology, 2021)
This is a retrospective cohort study included 1021 patients underwent a flexible GnRH antagonist IVF protocol from January 2017 to December 2017 to explore the effect of a premature rise in luteinizing hormone (LH) level on the cumulative live birth rate. All patients included received the first ovarian stimulation and finished a follow-up for 3 years. A premature rise in LH was defined as an LH level >10 IU/L or >50% rise from baseline during ovarian stimulation. The cumulative live birth rate was calculated as the number of women who achieved a live birth divided by the total number of women who had either delivered a baby or had used up all their embryos received from the first stimulated cycle. In the advanced patients (≥37 years), the cumulative live birth rate was reduced in patients with a premature rise of LH (OR: 0.20; 95% CI: 0.05–0.88; p=0.03), compared to patients (≥37 years) without the premature LH rise. The incidence of premature LH rise is associated with decreased rates of cumulative live birth rate in patients of advanced age (≥37 years) and aggravated the reduced potential of embryos produced by the advanced age, not the number of embryos.